STUDI CEMARAN MIKROBA PADA PRODUK PANGAN TRADISIONAL “LAWAR PUTIH DAGING BABI” DI KECAMATAN DENPASAR UTARA - Agustini, Ni Ketut Sri; Putra, I Nengah Kencana; Permana, Dewa Gde Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
The aim of this study was to know microbial contamination of white lawar pork and hygiene sanitation practices in some restaurants that sell white lawar pork in North Denpasar subdistrict. The study used a survey method with simple random sampling technique. Sampling was carried out in several restaurants in the North Denpasar subdistrict. The result from this research was served in table, and the data was analyzed by descriptive method. The variables observed were total microbes, E . coli , and Staphylococcus aureus . The results showed that as 45% of white lawar comply the total microbial requirements of processed meat with heat treatment in Indonesia (< 1x10 6 koloni/g), 100% lawar did not comply the requirements of E . coli in processed meat with heat treatment in Indonesia, and 100% white lawar had comply the requirements of Staphylococcous aureus in processed meat with heat treatment in Indonesia. 100% of lawar is processed in the morning. The practice of sanitation and hygiene at restaurants in the district of Denpasar Utara is quite good. Keywords: white lawar, microbial contamination, hygiene sanitation